A BIM-based intelligent approach to rebar layout optimization for reinforced concrete columns - Widjaja, Daniel Darma; Rachmawati, Titi Sari Nurul; Kim, Sunkuk (Journal of Building Engineering, 2025)
This study aims to address inefficiencies and errors in current manual rebar practices within the architecture, engineering, and construction (AEC) industry, which contribute to significant rebar waste. The Design-Bid-Build (DBB) project delivery method further exacerbates these issues by hindering effective stakeholder collaboration. By contrast, integrated project delivery and building information modeling (BIM) have shown potential for enhanced coordination and waste reduction. Yet, the continued reliance on manual rebar modeling in BIM highlights a pressing need for intelligent automation. This study presents a novel BIM-based algorithm that leverages Dynamo for rebar layout optimization and Navisworks for automatic clash detection, integrating rebar optimization prior to BIM model creation to minimize data exchange errors. The methodology was validated on a continuous-column rebar arrangement, supported by a standardized rebar summary sheet to streamline the optimization and clash-detection process. Key findings indicate that this approach significantly reduces working hours while achieving high modeling accuracy compared to traditional manual methods. These results highlight the potential of the proposed framework to transform rebar layout practices, enabling smart, efficient, and sustainable construction through automated clash-free rebar layout generation. [Display omitted] •Design-Bid-Build limits collaboration, increasing rebar waste in construction.•While IPD-BIM improves workflows, manual rebar modeling remains prevalent.•Dynamo and Navisworks optimize rebar layout for continuous column designs.•The rebar summary sheet standardizes and supports the Dynamo script.•Improved model accuracy and reduced working hours highlight efficiency gains.